Knowledge Level and Determinants Factors in Selecting to the Islamic Rural Banks - Egi Arvian Firmansyah; Amelia Rizky Alamanda; Teguh Santoso (International Journal of Islamic Business and Economics (IJIBEC), 2020)
The aims of this research are fourfold. First, it aims to identify the source of knowledge of the respondents on Islamic rural banks. Second, this research aims to study the factors considered important by the respondents in selecting Islamic rural banks. Third, this research studies the level of knowledge and awareness of the respondents on the products or contracts of Islamic rural banks. Finally, this paper aims to compare the respondents’ knowledge and awareness based on gender, education level, and period of banking in Islamic rural banks. We disseminated questionnaire to 285 customers of Islamic rural banks in several cities in West Java, Indonesia. This research uses descriptive and quantitative methods using a t-test. We found that our respondents attained knowledge in Islamic rural banks in college, and the most substantial factor affecting them to choose Islamic rural banking is not sharia compliance. In fact, it is the economic factor. Qardhul Hasan, wadiah, and mudharabah are the three most popular contracts among our research respondents. Finally, the level of knowledge and awareness about these three contracts are not significantly different between male and female, between different education levels, and between the banking periods of the customers.